Opening the black box of link formation: social factors underlying the structure of the web - González-Bailón, S (Elsevier, 2009)
Links play a twofold role on the web: they open the channels through which users access information, and they determine the centrality of sites and their visibility. This paper adds two factors to the analysis of links that aim to draw a parallel between the web and other offline interorganisational networks: the resources that the organisations publishing online are able to mobilise, and the status or public recognition of those organisations. Exponential random graph models (ERGMs) are used to analyse a sample of the web of about one thousand sites, showing that both the economic resources of the producers of the sites (a proxy to their wider pool of resources) and their presence in traditional news media (a proxy to their status) significantly increase their probability of receiving more links, and therefore, their centrality. This adds a sociologically relevant dimension to the analysis of the web that has been disregarded so far but that is crucial to understand the way it distributes visibility.